2022
DOI: 10.1021/acs.jafc.1c05029
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin Biosynthesis and a Regulatory Network of Different-Colored Wheat Grains Revealed by Multiomics Analysis

Abstract: Colored wheat has always been a popular research area because of its high performance in the field and significant medical uses. Progress has been made mapping the genes of purple or blue grains; however, the reason why different grain colors form in wheat is not well understood. We created wheat lines with different grain colors (purple and blue) using the white grain cultivar Xiaoyan22 and located the candidate region related to the purple and blue grains in chromosome 2A, 2B, and 4D, 2A, respectively, by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…PAL is a rate-limited enzyme engaged in the phenylalanine metabolism and catalyzes the conversion of L-phenylalanine to trans-cinnamic acid in the anthocyanin biosynthesis pathway [ 42 ]. There is enough evidence to suggest that the expression levels of PAL genes are associated to anthocyanin accumulation in plant tissues [ 72 , 73 , 74 , 75 , 76 , 77 ].The pal1 pal2 mutant Arabidopsis was reported to accumulate little anthocyanin pigments when plants were grown in under-fertilized and relatively low-temperature conditions, suggesting a redundant and important role of these two genes in anthocyanin biosynthesis [ 78 ]. More particularly, PAL genes have been shown to play a specialized role in anthocyanin biosynthesis in response to low temperature, through investigation of these genes using gene expression profiling, enzymatic activity assessment, omic survey and promoter functional analysis.…”
Section: Discussionmentioning
confidence: 99%
“…PAL is a rate-limited enzyme engaged in the phenylalanine metabolism and catalyzes the conversion of L-phenylalanine to trans-cinnamic acid in the anthocyanin biosynthesis pathway [ 42 ]. There is enough evidence to suggest that the expression levels of PAL genes are associated to anthocyanin accumulation in plant tissues [ 72 , 73 , 74 , 75 , 76 , 77 ].The pal1 pal2 mutant Arabidopsis was reported to accumulate little anthocyanin pigments when plants were grown in under-fertilized and relatively low-temperature conditions, suggesting a redundant and important role of these two genes in anthocyanin biosynthesis [ 78 ]. More particularly, PAL genes have been shown to play a specialized role in anthocyanin biosynthesis in response to low temperature, through investigation of these genes using gene expression profiling, enzymatic activity assessment, omic survey and promoter functional analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Three redundant MYB family members regulate flavonoid biosynthesis by activating the genes for early anthocyanin biosynthesis, and the MYB-bHLH-WD40 (MBW) complex is required to activate late biosynthetic steps for anthocyanin production in Arabidopsis . ,, Two transcription factors, TaPpm1 (MYB) and TaPpb1 (bHLH), have been reported to coregulate the biosynthesis of anthocyanins in purple wheat . The up-regulated expression of TaMYC1 and TaMYC4 promotes color formation in purple and blue wheat grains . A recent study reports that anthocyanin biosynthesis and Se metabolism could be regulated by the same MYB and bHLH at the transcriptional level in wheat .…”
Section: Discussionmentioning
confidence: 99%
“…76 The upregulated expression of TaMYC1 and TaMYC4 promotes color formation in purple and blue wheat grains. 77 A recent study reports that anthocyanin biosynthesis and Se metabolism could be regulated by the same MYB and bHLH at the transcriptional level in wheat. 24 S 4 A 0 2 G 0 0 6 1 0 0 , T r a e s C S 4 B 0 2 G 2 9 9 0 0 0 a n d TraesCS4D02G297900) are CSA-like genes and are involved in flavonoid accumulation and pigment production.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The regulation of anthocyanin biosynthesis has been an area of significant interest. Genes involved in the anthocyanin biosynthesis pathway are regulated by ternary MYB-bHLH-WD40 complexes (MBW) formed by R2R3-MYB transcription factors, bHLH transcription factors, and WD40 proteins ( 32 , 33 ). Jiang et al ( 16 ) revealed their cooperation to modulate anthocyanin production in the wheat purple pericarp.…”
Section: Origin and Genetics Of Anthocyanin Accumulation In Colored W...mentioning
confidence: 99%